Molecular simulation of adsorption behaviors of methane and carbon dioxide on typical clay minerals - Hui, Dong; Li, Longxin; Zhang, Yan; Peng, Xian; Li, Tao; Jia, Changqing; Pan, Yi (Frontiers in Energy Research, 2023)
Knowledge of the interaction mechanisms between shale and CH4/CO2 is crucial for the implementation of CO2 sequestration with enhanced CH4 recovery (CS-EGR) in shale reservoir. As one of the main constituents of shale, clay minerals can profoundly affect the storage capacity of gases in nanopores. In this paper, the adsorption behaviors of both CO2 and CH4 on montmorillonite, illite as well as kaolinite under dry condition are investigated by Grand Canonical Monte Carlo (GCMC) simulation. The results exhibit that the maximum adsorption capacity of single-component CH4 and CO2 is associated with the types of clay crystals. Specifically, the montmorillonite has the strongest adsorption capacity for CO2, followed by illite and kaolinite, while the sequence in maximum adsorption capacity of CH4 is predicted in the order of kaolinite > montmorillonite > illite. These discrepancies are closely related to the characteristics of adsorbate molecules as well as the different structures of clay crystals. Meanwhile, the maximum adsorption capacity of CH4 in studied clay minerals gradually decreases as pore size increases, while nanopores with 2-nm basal spacing demonstrate the highest adsorption capacity for CO2. In addition, it is observed that the studied clay minerals tend to preferentially adsorb CO2 rather than CH4 during binary gas mixtures simulation. The selectivity of CH4/CO2 mixtures in montmorillonite and kaolinite exhibits various performances as the adsorption pressure increases, with the selectivity in montmorillonite being the largest, especially at low pressure. The cation exchange significantly enhances the electrostatic interaction with CO2 molecules, leading to a higher loading of CO2 as well as larger value of selectivity. These findings can provide basis and guidance for the CS-EGR project in shale reservoirs.